2001
DOI: 10.1164/ajrccm.164.5.2012122
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hyperinflation and Exercise Intolerance in Chronic Obstructive Pulmonary Disease

Abstract: The role of dynamic hyperinflation (DH) in exercise limitation in chronic obstructive pulmonary disease (COPD) remains to be defined. We examined DH during exercise in 105 patients with COPD (FEV(1) = 37 +/- 13% predicted; mean +/- SD) and studied the relationships between resting lung volumes, DH during exercise, and peak oxygen consumption (VO(2)). Patients completed pulmonary function tests and incremental cycle exercise tests. We measured the change in inspiratory capacity (Delta IC) during exercise to ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
754
6
36

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 910 publications
(840 citation statements)
references
References 28 publications
44
754
6
36
Order By: Relevance
“…However, the extent of the reduction in IC with exercise in COPD is variable. In a population of 105 patients with moderate-to-severe COPD, IC at end-exercise was reduced by 20% of its already-reduced resting value [81], as exemplified in figure 1. In another smaller group of 27 severe COPD patients, a similar reduction was found at the end of high-intensity exercise [80].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 94%
“…However, the extent of the reduction in IC with exercise in COPD is variable. In a population of 105 patients with moderate-to-severe COPD, IC at end-exercise was reduced by 20% of its already-reduced resting value [81], as exemplified in figure 1. In another smaller group of 27 severe COPD patients, a similar reduction was found at the end of high-intensity exercise [80].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 94%
“…Breathing pattern (timing, flow, and volume measurements) and dynamic IC were measured using the SensorMedics Vmax229 system as previously described (38). Operating lung volumes and their changes during exercise were derived from measurements of dynamic IC that were performed at rest, within the last 30-s period of each increment of exercise, and at peak exercise.…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%
“…Lung IC has been shown to correlate significantly with increased exercise endurance and with reduced dyspnoea during exercise 5,19 . It has been shown that the reduction in breathlessness during exercise and improved exercise tolerance are closely related to the bronchodilator-induced change in IC at rest, regardless of the change in resting FEV 1 20 .…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%